Unveiling the anticancer potential of the ethanolic extract from Trichoderma asperelloides - Oliveira, Ana Carolina R.; De Oliveira, Flávia Santiago; Bráz, Ana Flávia; Oliveira, Jamil S.; Lima-Santos, Jane; Dias, Adriana A. M. (Frontiers in Pharmacology, 2024)
The discovery of new therapeutic alternatives for cancer treatment is essential for improving efficacy and specificity, overcoming resistance, and enabling a more personalized approach for each patient.We investigated the antitumor activity of the crude ethanolic extract of the fungus Trichoderma asperelloides (ExtTa) and its interaction with chemotherapeutic drugs. ExtTa significantly reduced cell viability in breast adenocarcinoma, glioblastoma, lung carcinoma, melanoma, colorectal carcinoma, and sarcomas cell lines. The highest efficacy and selectivity of ExtTa were found against glioblastoma T98G and colorectal HCT116 cell lines. A synergistic effect between the ExtTa and the doxorubicin was found in the treatment of osteosarcoma Saos-2 cells, as well as with 5-fluorouracil in the treatment of HCT116 colorectal carcinoma cells. Our data unravel the presence of bioactive compounds with cytotoxic effects against cancer cells present in T. asperelloides ethanolic crude extract, with the potential for developing novel anticancer agents.